Psychological strategies in managing television commercial efficacy (2001)
This paper examined advertisement presentation frequency (repetitive Versus non-repetitive), type of stimulus (familiar versus novel), and information source (credible versus non-credible) as psychological strategies of managing television commercial efficacy. Subject’s total score on recall of advert information, attitude to an advert, and intention to buy an advertised product was used as a measure of advertisement efficacy. By employing 2x2x2 factoral design, eight advert pieces were designed to reflect the levels of the independent variable. The result of the 2x2x2 analysis of variance (ANOVA) computed showed significant main effect of each of the independent variables on the dependent variable. Except the interaction effect between representation frequency and information source, all others were significant. It was finally suggested for advertisement practitioners to repeat advert messages, use familiar stimulus background information and perceived credible persons in disseminating advert messages. A total of 80 (40 males, 40 females) randomly selected secondary school students were used for the study.